Rehabilitation exercise for treatment of vestibular disorder: A case study - Avraham Feazadeh; Eli Carmeli (The Scientific World Journal)
Vertigo and dizziness are common symptoms in the general population. While the clinical picture is well known and widely described, there are different interpretations of Benign Paroxysmal Positional Vertigo. The purpose of this case report was to describe the treatment of a 56 year old woman with complains of positional vertigo for 35 consecutive years. She suffered from a sudden onset of rotatory, unilateral horizontal canal type benign paroxysmal positional vertigo (BPPV). The symtoms started a day after falling from a bus, where she injured her head. Otherwise her medical history was unremarkable. She was treated with an individualized home exercise program of eye movement exercises, Brandt/Daroff exercises, and general conditioning exercises (i.e., laying on the left side from sitting on the bed, while the head rotated 45 degrees to the right, waiting for about one minue; twice a day on gradual basis, not laying on the side all the way, but to use enough pillows to lay about at 60 degrees). Four weeks from the start of physical therapy, the patient was free of symptoms, even when her neck was in the extended position.